The Measurement of Experience and Satisfaction with Public Provision of Assistive Technology Services for Workers with Disabilities in Korea - Moookong, Jeon (Technium Social Sciences Journal, 2023)
The Korean government has been providing AT services for workers with disabilities and is increasing its provision every year. However, there are request for improvement from individuals with disabilities regarding service process, eligibility, and quality of services. In response to those requests, this study was created to more accurately identify the process to be improved and to collect opinions from workers with disabilities for improvement of public AT services. The survey consisted of respondents’ demographic information, experiences with the public AT service process, and opinions on improving public AT service. The request to participate in the survey was conducted for 3 weeks, and the responses of 158 disabled workers were used for analysis. This study used descriptive statistics and analysis of variance and planned follow-up testing in case a significant difference was found. The results indicated a low satisfaction with early stages of AT service process, such as information acquisition. Respondents also hoped that the application process would be changed to be simpler and more direct to take into account workers with disabilities, and that the provision of assistive devices would be expanded and diversified. The government is leading positive changes in line with the needs of workers with disabilities identified in this study. In the future, it is necessary to gradually expand the application eligibility for public AT services and to improve service system and provide government support for them.